Emotions and interactive tangible tools for math achievement in primary schools - Saccardo, Filippo; Decarli, Gisella; Missagia, Valentina Irene; Andrao, Margherita; Gini, Federica; Zancanaro, Massimo; Franchin, Laura (Frontiers in Psychology, 2024)
Introduction Acquiring mathematical concepts is crucial for students’ academic achievements, future prospects and overall well-being. This study explores the role of emotions in a symbolic number comparison task and the impact of the use of a tangible tool. Methods Fifty-nine healthy children aged 6 to 7 years participated in a between-subject study with two conditions for the modality, digital tools vs the use of pen and paper, and two conditions for emotions, positive vs neutral. Results The study provided evidence that positive emotions can improve task efficiency for pen and paper modality, and the use of the digital tool improves task efficiency with both positive and negative emotions. Discussion These findings suggest that addressing emotional factors before engaging in a symbolic task can enhance learning and that interactive technology may give a more significant benefit to students with less positive attitudes toward the task. Incorporating effective teaching methodologies that utilize tangible devices within a positive emotional context can foster engagement and achievement in mathematics, optimizing students’ learning experiences.